Parametric Marcinkiewicz Integral and Its Higher-Order Commutators on Variable Exponents Morrey-Herz Spaces. (14th September 2022) - Omer, Omer Abdalrhman; Saibi, Khedoudj; Abidin, Muhammad Zainul; Osman, Mawia
Abstract : In this article, we prove the boundedness of the parametric Marcinkiewicz integral and its higher-order commutators generated by BMO spaces on the variable Morrey-Herz space. All the results are new even when α · is a constant.